1993
DOI: 10.1111/j.1748-1090.1993.tb00614.x
|View full text |Cite
|
Sign up to set email alerts
|

The Wetland Aviary at Rheine Zoo

Abstract: A walk-through aviary opened at Rheine Zoo in 1984 was designed to simulate a wetland habitat housing egrets, ibises and spoonbills. The paper details the construction and management of the exhibit which, in addition to breeding colonies of birds, sustains appropriate flora, invertebrate and fish populations. Winter quarters and management are also described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Salzert & Johann () reported that moving birds to a wetland aviary at Rheine Zoo, Germany, greatly reduced the amount of keeper time needed for regular enclosure maintenance in comparison with the time needed when these birds were kept in smaller enclosures. There are economic and time‐management constraints involved in repeated capture and treatment of large numbers of birds for which temporary flight‐restraint methods are used (Hesterman et al ., ).…”
Section: Reasons For Choosing Aviaries As Enclosuresmentioning
confidence: 99%
“…Salzert & Johann () reported that moving birds to a wetland aviary at Rheine Zoo, Germany, greatly reduced the amount of keeper time needed for regular enclosure maintenance in comparison with the time needed when these birds were kept in smaller enclosures. There are economic and time‐management constraints involved in repeated capture and treatment of large numbers of birds for which temporary flight‐restraint methods are used (Hesterman et al ., ).…”
Section: Reasons For Choosing Aviaries As Enclosuresmentioning
confidence: 99%